Evaluation of ureterorenoscopy with semirigid ureteroscope and laser lithotripsy as a treatment modality for upper ureteric stones less than 20 mm - Ravi Batra; Pooja Batra; Shreyak Garg; Sneha Yadav (Wolters Kluwer Medknow Publications, 2021)
Context: Technological developments over the past two decades have revolutionized the treatment of ureteric stones. With the emergence of flexible, small-diameter ureteroscopy, the paradigm of ureteral stone treatment has shifted to ureteroscopy. The success rate is close to 95%, but it has its own complications. Objective: The objective of this study is to assess the effectiveness of ureterorenoscopy (URS) with semirigid ureteroscope and laser lithotripsy in the treatment of upper ureteric stones of size less than 20 mm and its associated complications. Methods: This is a prospective cohort study designed to assess the effectiveness of URS for the treatment of upper ureteric calculi. We present data from 57 patients who received URS as their primary treatment at our center and were followed up for at least 3 months. Results: We found that when stone size was less than 10 mm, the stone-free rate was 80% (28/35), while when stone size was in the 10.1-20 mm range, the stone-free rate increased to 90.9% (20/22). Stones were found in 41/48 patients (85.41%) with symptoms lasting less than a month. Only 7/9 patients (77.77%) were stone-free in the group with symptoms lasting more than a month. A total of 28.1% of patients encountered complications among which proximal migration of the stone was the most common (12.3%). Mean procedure time was 40.37 min. Conclusion: This study shows that URS had a higher stone-free rate when treating stones of size ranging from 10.1 to 20 mm. In upper ureteric stones ranging in size from 10.1 to 20 mm, we strongly advise using URS as the primary treatment option.